Digital resources to teaching and learning English as a Foreign Language in remote classes - de Deus Rocha, Vanessa; Garbin Baldissera, Luana; Araújo Rosa Filho, Jeová (Revista X, 2021)
Education is one of the areas which has been most impacted by the COVID-19 pandemic, as the social distancing measures adopted by governments affected 90% of the student population worldwide. The solution found by many educational institutions, including in the Brazilian context, was to adopt Emergency Remote Education (ERE), despite the challenges related to the access to internet and digital technological resources, and the lack of teacher training regarding their use. Having this in mind, this article aims at discussing the concept of ERE, as well as to present and discuss digital technological resources such as platforms and apps which may be used by language teachers to support their pedagogical practice, promoting language development through interaction, increase motivation and learner’s autonomy. The article ends presenting the development of a digital story as an activity that may be accomplished through the use of apps.